2022
DOI: 10.1371/journal.pone.0262903
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B, C and D virus infections and risk of hepatocellular carcinoma in Africa: A meta-analysis including sensitivity analyses for studies comparable for confounders

Abstract: Introduction Africa denotes unique facies for hepatocellular carcinoma (HCC) characterized by a conjunction of low sensitization, restricted access to diagnosis and treatment and associated with the highest incidence and mortality in the world. We investigated whether hepatitis B (HBV), C (HCV) and D (VHD) viruses were etiological agents of HCC in Africa. Methods Relevant articles were searched in PubMed, Web of Science, African Index Medicus, and African Journal Online databases, as well as manual searches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 64 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…In South Africa, many HBV infections aren’t discovered in PLWH until these individuals are diagnosed with HCC. As a result, many individuals appear with several lesions or large liver lesions on radiological examination, thus limiting the treatment options to palliative strategies [ 8 ] . Similarly, according to one study carried out in Egypt there is no efficient screening strategy for HCC in cirrhotic individuals with HIV, with only ~10% of new HCC detected during planned screening, while 38% of these patients had multiple liver tumors, and 72% had tumors greater than 5 cm in diameter [ 74 ] .…”
Section: Hcc Surveillance In Hiv-hbv Coinfected Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…In South Africa, many HBV infections aren’t discovered in PLWH until these individuals are diagnosed with HCC. As a result, many individuals appear with several lesions or large liver lesions on radiological examination, thus limiting the treatment options to palliative strategies [ 8 ] . Similarly, according to one study carried out in Egypt there is no efficient screening strategy for HCC in cirrhotic individuals with HIV, with only ~10% of new HCC detected during planned screening, while 38% of these patients had multiple liver tumors, and 72% had tumors greater than 5 cm in diameter [ 74 ] .…”
Section: Hcc Surveillance In Hiv-hbv Coinfected Patientsmentioning
confidence: 99%
“…Africa and East Asia are estimated to account for more than 75% of global HCC patients [ 6 ] . Indeed, unique risk factors, such as a high prevalence of HIV in the context of HBV or hepatitis C (HCV) coinfection, as well as exposure to aflatoxins and underreported consumption of alcohol help explain the high incidence of HCC in these regions [ 6 8 ] . Moreover, the dynamics related to poor outcomes in HCC are increased in resource-limited settings including many parts of Africa, where most of HIV infections occur [ 9 , 10 ] .…”
Section: Introductionmentioning
confidence: 99%
“…Although the prevalence of NAFLD is increasing globally and emerging as a major cause of advanced liver diseases, effective and evidence-based pharmacotherapy is still lacking [ 4 ]. In viral hepatitis, potent antiviral therapy using nucleot(s)ide analogues and direct-acting antivirals (DAAs) is the mainstay treatment; however, only selected patients are candidates for antiviral therapy, and the supply of antiviral drugs is often limited in under-developed countries [ 5 , 6 ]. In addition, research has shown the combined fatty load in patients with viral hepatitis to have an unfavorable influence on long-term outcomes [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…4 In viral hepatitis, potent antiviral therapy using nucleot(s)ide analogues and direct-acting antivirals (DAAs) is the mainstay treatment; however, only selected patients are candidates for antiviral therapy, and the supply of antiviral drugs is often limited in under-developed countries. 5,6 In addition, research has shown the combined fatty load in patients with viral hepatitis to have an unfavorable influence on long-term outcomes. 7 Therefore, varying drugs, including antidiabetics, antioxidants, lipid-lowering drugs, probiotics, and anti-platelets, which might have potential beneficial effects, have been continuously investigated in patients with CLD.…”
Section: Introductionmentioning
confidence: 99%
“…In Africa, HBV and HCV are the primary HCC aetiologic agents (2,9,10), with over half of HCC cases caused by HBV, while approximately 25% are caused by HCV (10); however, in some African countries, Egypt in particular, HCV is the leading cause of HCC (11). Unfortunately, in Sub-Saharan Africa, most HCC diagnosis is made late in the disease cycle when surgery cannot be done.…”
Section: Introductionmentioning
confidence: 99%